Study of disinfectant activity against bee pathogenic enterobacteria in vitro - T. A. Romanishina; A. R. Lakhman; O. Ye. Galatiuk; V. L. Behas; M. V. Zastulka (Ukrainian Journal of Veterinary and Agricultural Sciences, 2024)
Dysbiosis is a pathological condition caused by violating the normal coexistence of bacterial organisms in one or more body systems. This disease arises due to the action of many ethological factors, the mechanisms of which arise from each other. Klebsiellosis of bee colonies is a relatively new disease of Apis mellifera, caused by pathogenic enterobacteria, which leads to the mass death of bees with signs of acute dyspepsia, particularly in the spring and autumn periods. To prevent klebsiellosis in bees, it is necessary to carry out veterinary and sanitary measures in apiaries every year, including disinfection. Modern beekeeping encourages the search for new antibacterial drugs to ensure the production technology of safe and high-quality beekeeping products suitable for sale. Preliminary laboratory assessment (in vitro) of the effectiveness of disinfectants against specific pathogens of specific diseases of bees will ensure an increase in the effectiveness of such agents in apiaries, which is economically effective for practical beekeeping. The purpose of the research was to determine the activity of different concentrations of the disinfectant (0.25 %, 0.5 %, 1.25 %, 2.5 %) with an active substance of an organic nature with covalent weakly polar bonds against pure cultures of pathogenic enterobacteria of bees of the species Klebsiella pneumoniae and Klebsiella (Enterobacter) aerogenes in vitro. The modified Kirby-Baur method on Mueller-Hinton agar was used for research. A bactericidal effect against a pure culture of Klebsiella pneumoniae species was registered after 24 hours with lysis zone diameters at 8.6 ± 0.27 mm (0.25 % concentration) – 15.0 ± 0.35 mm (2.5 % concentration). On the 3rd day of research, a bacteriostatic effect was registered with the largest diameter of the zone of growth retardation (24.4 ± 0.27 mm) at 2.5 % disinfectant concentration. Bactericidal and bacteriostatic effects were recorded on the culture of enterobacteria of bees of the species Klebsiella (Enterobacter) aerogenes for 24 hours of cultivation with zones of lysis – 6.8 ± 0.42 mm (0.25 %) – 11.8 ± 0.22 mm (2.5 %) and inhibition of bacterial growth at the level of – 21.8 ± 0.42 mm (0.25 %) – 25.8 ± 0.42 mm (2.5 %). At the same time, there was no significant difference between the zones of Klebsiella (Enterobacter) aerogenes growth retardation in concentrations of 0.5 % – 2.5 % on the 3rd day of research. The studied disinfectant has bactericidal and bacteriostatic effects on pure cultures of bee enterobacteria of the species Klebsiella pneumoniae and Klebsiella (Enterobacter) aerogenes in laboratory conditions, which is promising for further study of the drug.